Management of Generalized Vitiligo in Adolescent with Tofacitinib: Clinical Case - Eduard T. Ambarchyan; Anastasiya D. Kuzminova; Vladislav V. Ivanchikov; Aleksandra A. Rogova (Вопросы современной педиатрии)
Background. Vitiligo is a depigmenting skin disease characterized by selective loss of melanocytes leading to development of typical white spots. There are various theories on vitiligo etiology: genetic, autoimmune, neurogenic, autoinflammatory, oxidative stress theory, and many others. Generally accepted dominant role is given to the concept of its autoimmune nature. Vitiligo management traditionally includes different methods of phototherapy, topical and systemic glucocorticoids (GC), and calcineurin inhibitors. Recently, Janus kinase inhibitors (JAK) have shown its efficacy in treatment of vitiligo. Clinical case description. 13-year-old male adolescent has complaints of hypopigmentation areas on the skin of face, trunk and limbs that appeared after active solar insolation during summer vacation. Dermatologist has determined a diagnosis of vitiligo according to clinical picture. Topical GC of the 3rd activity class were used for treatment, as well as course of local narrow-band medium-wave photodynamic therapy (311 nm, No. 30) with no significant effect. The patient was admitted to the dermatology department of Research Institute of Pediatrics and Children’s Health in Petrovsky National Research Centre of Surgery where therapy with JAK inhibitor, tofacitinib, was initiated due to inefficacy of previous treatment and the generalized form of the disease. Conclusion. Management of vitiligo with JAK inhibitors, in particular tofacitinib, is a promising method and it can lead to significant clinical effect with safety profile comparable to conventional therapies for this pathology.